Surface charge induced self-assembled nest-like Ni3S2/PNG composites for high-performance supercapacitors - Li, Guifang; Fan, Xiaohong; Deng, Dingrong; Wu, Qi-Hui; Jia, Lishan (Journal of colloid and interface science, 2023)
[Display omitted] •A nest-like composite Ni3S2/PNG-10 with high structural stability was synthesized by surface charge induction.•The Ni3S2/PNG-10 shows high specific capacitance and outstanding stability.•Asymmetric electrochemical capacitor device exhibits an energy density of 62 Wh kg−1. The paper presents a self-assembly approach to synthesize Ni3S2/N, P co-doped graphene (PNG) composite electrode materials for supercapacitors with high energy storage performance and structural stability. Innovatively, the self-assembly approach is induced via the surface charge effect utilizing a two-step hydrothermal method. The doping of nitrogen (N) and phosphorus (P) atoms regulates the surface charge distribution on graphene nanosheets. Therefore, in the synthesized Ni3S2/PNG heterostructures, Ni3S2 nanowires are interwoven into nests and uniformly attached to PNG. The design of the electrode materials with such a special structure not only supports each other to improve the stability of the materials but also facilitates the rapid diffusion of electrolyte ions. Based on the advantages of composition and structure, Ni3S2/PNG has a high specific capacitance of 1117C g−1 at a current density of 1 A/g and excellent rate performance. The asymmetric supercapacitors (ASC) assembled with Ni3S2/PNG and PNG as positive and negative materials respectively have a high energy density of 62 Wh kg−1 at a power density of 158 W kg−1.